Ação da fosfolipase B extracelular de Paracoccidioides brasiliensis na interação ex vivo com macrófagos alveolares - SOARES, Deyze Alencar (2010)
Paracoccidioides brasiliensis, a thermodimorphic fungus, is the causative agent of the most prevalent systemic mycosis in Latin America, paracoccidioidomycosis. The phospholipase B (PLB) enzyme is considered an important virulence factor in this dimorphic fungus, involved in the immune response of the host-pathogen interaction. Our objective was to determine whether a P. brasiliensis (Pb18) PLB is involved in adhesion / internalization of yeast and evasion of host immune responses. The effect of PLB was analysed using specific inhibition of PLB (alexidine dihydrochloride) and pulmonary surfactant in an ex vivo model (Pb18) of alveolar macrophage (MHS cells) infection. PLB enzyme assays and real time RT-PCR (qRTPCR) analysis of genes differentially expressed in the process of evasion: plb1 (phospholipase B1), icl1 (isocitrate lyase) and sod3 (Cu, Zn dismutase) and immune responses: clec2 (C-type lectin domain 2), cd14 (cluster of differentiation 14), tlr2 (toll-like receptor 2), nfkb (nuclear factor kappa B), nkrf (NF-kappaB repressing factor), il1β (inteleukin-1β) and tnfα (tumor necrosis factor alpha) were carried out using selective inhibition of PLB activity and pulmonary surfactant. The levels of cytokines inteleukin 10 (IL-10), IL-12 and TNF-α) were also determined by ELISA. PLB activity under adhesion conditions of P. brasiliensis (Pb18) to alveolar macrophage cells was found at high levels up to 6 hours post-infection. In the conditions of exposure to pulmonary surfactant and alexidine dihydrochloride, PLB activity and the level of transcripts of genes related to phagocytosis and inflammatory response were measured. We found that PLB activity had an influence on the phagocytic activity of alveolar macrophages. Alexidine dihydrochloride (0,25 μM) selectively inhibited PLB activity by 66% and decreased significantly the adhesion and internalization of yeast on MHS cells. Genes involved in phagocytosis (trl2 and cd14) and inflammatory response (nrkf, tnfα and il1β) were down-regulated in the presence of the PLB inhibitor. In contrast, the PLB activity and internalization of fungal yeast cells increased significantly in the presence of pulmonary surfactant (100 μg/mL) and genes such as clec2, important for effective phagocytosis by MHS cells, and the pro-inflammatory inhibitor (nkrf) were up-regulated. Also, the pulmonary surfactant did not alter cytokine production, while alexidine dihydrochloride decreased the levels of IL-10 and increased the levels of IL-12 and TNF-α. In addition, through simultaneous analyses of gene expression for the pathogen, P. brasiliensis, we found upregulation of the genes sod3, icl1 and plb1, required for the evasion of alveolar macrophages. P. brasiliensis PLB is important for the binding and internalization of yeast at macrophage surfaces. The specific effect of inhibiting PLB enzyme activity indicates that adhesion may be facilitated indirectly via fatty acid release from phospholipids of the membrane of host cells. This is the first study to show that PLB activity may modulate immune responses to P. brasiliensis infection.